Entrepreneurial Behaviour of Tribal Dairy Farmers in Balrampur District of Northern Hill Region of Chhattisgarh - Gupta, Ravi Kumar; Saha, Anindita; Tiwari, Pravin Kumar; Dhakre, Digvijay Singh; Gupta, Ankur (Indian Journal of Extension Education, 2019)
Entrepreneurs play an important role in the economic development of the society. The study was conducted during 2018-19 to know the entrepreneurial behaviour of tribal dairy farmers in Balrampur District of northern hill region of Chhattisgarh. The data were collected by pre-tested interview schedule from 120 interviewees. The results of the study found that majority of the respondents exhibited medium level (72.50%) entrepreneurial behaviour. The correlation of entrepreneurial behaviour among the eighteen independent variables; only seven variables (Land Holding, Mass Media, Income Status, Herd Size, Total Milk Production, Milk Sale and Attitude) showed the positive significant relationship. Regression analysis had shown all the 18 independent variables put together have influenced significant variation in entrepreneurial behaviour to the extent of 35.10 per cent. Path analysis approach depicted that total milk production had the highest total effect on entrepreneurial behaviour followed by Income Status and Landholding.
Keywords: Dairy farming; Entrepreneurial behaviour; Path analysis; Socio-economic status; Tribal dairy farmers